여성정신질환자의 지역사회전환시설 입소 및 지역사회 복귀 실태 (2016-2018년) - 최유진; Yoo Jin Choi; 김경희; Gyung Hee Kim; 김윤수; Yunsoo Kim; 박민석; Minseok Park (보건정보통계학회지, 2021)
This study aims to understand the characteristics and actual conditions of female mentally ill patients using the halfway house and provide them with primary data to utilize the halfway house as an integrated approach within the mental health delivery system. Methods: This study’s subject is the case management record of 434 female mentally ill patients admitted to halfway house in Seoul from January 1, 2016, to December 31, 2018. Collected data were analyzed using SPSS Win 22.0 program. Results: The average age of subjects using halfway house was 44.2 years old, and 67.3% of the admission period was less than one month. 44.7% of the residential situation was in-home residence, and 41.0% of pre-admission job was the unemployed. and the most common type of social security was the medical benefit (65.7%). The most common onset of mental illness was in their twenties (44.5%), and the most common in diagnosing mental illness was schizophrenia spectrum disorder (89.4%). Those who did not receive the grade was 56.5% and grade of mental disorder was 43.5%. The most common reason for dismissal when improved symptoms (91.2%). Conclusions: This study reviews halfway houses’ role and function and proposes a follow-up study on applying programs operating within the community transformation facilities.